2008
DOI: 10.1088/0264-9381/25/20/202002
|View full text |Cite
|
Sign up to set email alerts
|

DSR as an explanation of cosmological structure

Abstract: Deformed special relativity (DSR) is one of the possible realizations of a varying speed of light (VSL). It deforms the usual quadratic dispersion relations so that the speed of light becomes energy dependent, with preferred frames avoided by postulating a non-linear representation of the Lorentz group. The theory may be used to induce a varying speed of sound capable of generating (near) scale-invariant density fluctuations, as discussed in a recent Letter. We identify the non-linear representation of the Lor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 46 publications
4
48
1
Order By: Relevance
“…The minimal bimetric theory leads to scale-invariant perturbations but it is also possible to obtain deviations from strict scale-invariance, subject to consistency relations involving the 3-point function [29,30]. It is also possible to implement this mechanism via deformed dispersion relations [31], as we now review.…”
Section: Cosmological Perturbationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The minimal bimetric theory leads to scale-invariant perturbations but it is also possible to obtain deviations from strict scale-invariance, subject to consistency relations involving the 3-point function [29,30]. It is also possible to implement this mechanism via deformed dispersion relations [31], as we now review.…”
Section: Cosmological Perturbationsmentioning
confidence: 98%
“…In particular it is associated with Hořava-Lifshitz (HL) theory for an anisotropic scaling with dynamical critical exponent z = 3, a theory known to be power-counting renormalisable [4]. Before the advent of HL theory it was known [31] that this dispersion relation leads to a scale-invariant spectrum of density fluctuations without appealing to inflation. This important remark was later picked up in the context of HL theory [32], where it was noted that the result is independent of the assumption of detailed balance.…”
Section: Pervasiveness Of Scale-invariance For Ds =mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless there has been ongoing interest in whether the speed of light really is invariant (Albrecht & Magueijo, 1999;Barrow & Magueijo, 1999;Bassett, Liberati, Molina-Paris, & Visser, 2000;Clayton & Moffat, 2003;Magueijo, 2001Magueijo, , 2003Magueijo, , 2008Moffat, 2005;Singha & Debnath, 2007;Sisterna, 2011;Szydlowski & Krawiec, 2003;Unzicker, 2009). The primary purpose of these endeavours has been to explore for new physics at deeper levels, with a particular interest in quantum-gravity.…”
Section: Variable Speed Of Light Theoriesmentioning
confidence: 99%
“…They in fact describe effects that are quite generically expected in quantum gravity research [3,4] (and in particular have been explicitly shown to characterize 3D quantum gravity [5,6]) without introducing preferred frames and so evading the strong constraints on Lorentz invariance violations. Modified dispersion relations could produce observable phenomenology in the context of astrophysics [7][8][9][10][11] and there is also increasing evidence that they could be relevant in the early Universe [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%